Evaluation of Cervix at Risk with Pap Smear and with Colposcopy (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Unhealthy cervix is a very common finding in Bangladesh due to poor genital hygiene, malnutrition, and multiparity. Cervical Cancer is a serious health problem in Bangladesh and other developing countries. Cervical Cancer is a preventable cancer due to long preinvasive state and available cervical screening program like pap smear, colposcopy etc. Upon detection the treatment of pre-invasive lesions is highly effective. The objective of our study is to observe and evaluate suspicious cervix upon specimen collection by pap smear and viewing them by colposcopy when required.  Materials and methods: This is a descriptive type of observational cross-sectional study conducted in the Department of Obstetrics and Gynecology of BBMH, Chittagong over a period of six months from December 2020 to June 2021. A total of 64 women were selected, who came to hospital outdoor for the treatment of persistent vaginal discharge, post coital bleeding, postmenopausal bleeding. A thorough general, systemic and pelvic examination was done. Pap smear was conducted and colposcopy was done for women who had persistent inflammation on pap smear cases. Multiple variables like age of marriage and first intercourse, parity contraception was taken in consideration. The data obtained were recorded and statistically analyzed.                       Results: Out of 64 women the minimum age was 30 and maximum was 62 years with a mean age of 32.6 ± 7.2 years. Of the 64 women with unhealthy, inflammatory pap smear cases, 33 (51.6%) patients were colposcopically positive for CIN. Then histopathological evaluation of the biopsy material of those 33 women were done. It revealed 12 (36.3%) with abnormal cytology. Patients with positive CIN experienced early marriage, early age of child birth, and also had higher parities than patients without CIN.Conclusion: This study should that cervical lesion is one of the commonest problems among the females worldwide, including Bangladesh. This revealed the importance of emphasizing on proper screening of carcinoma cervix to decline incidence and mortality in developed and developing countries.JCMCTA 2022 ; 33 (1) : 71-76